Beta-adrenergic reactivity of erythrocyte membranes in various phenotypes of uncontrolled hypertension - M. A. Manukyan; A. Yu. Falkovskaya; V. F. Mordovin; I. V. Zyubanova; V. A. Lichikaki; E. I. Solonskaya; A. A. Vtorushina; S. A. Khunkhinova; I. A. Skomkina; V. V. Rudenko; T. Yu. Rebrova; E. F. Muslimova; et al. (Российский кардиологический журнал)
Aim. To assess the functional state of the sympathetic nervous system according to β-adrenergic reactivity of erythrocyte membranes (EM) in patients with refractory (rfHTN) and resistant hypertension (rHTN) in relation to target organ damage.Material and methods. The cross-sectional comparative study included 78 patients with uncontrolled hypertension (mean age, 57,4±9,3 years (33 men)) with 24-hour blood pressure (BP) (systolic/diastolic) of 160,0±18,8/88,1±17,3 mm Hg. Thirty-nine (50%) patients had type 2 diabetes (T2D). At baseline, patients were divided into 2 groups depending on the phenotype of uncontrolled hypertension. The first group consisted of patients with rfHTN (n=26 (33,3%)), the second — with rHTN (uncontrolled BP with 3-4 agent therapy) (n=52 (66,7%)). In all patients, office and mean 24-hour blood pressure, EM β-adrenergic reactivity and target organ damage were assessed.Results. The compared groups did not differ in sex and age composition, prevalence of T2D and basic clinical data. However, despite comparable levels of office and mean 24-hour blood pressure, the incidence of left ventricular (LV) hypertrophy according to echocardiography in rfHTN was significantly higher than in rHTN (96,2% vs 76,9%, p=0,027, respectively). An increase in EM β-adrenergic reactivity (>20 conventional units) was documented in 87,1% of patients in the general group. Moreover, the mean EM β-adrenergic reactivity in the rfHTN group was significantly higher than in the rHTN group (51,5±18,7 vs 39,3±18,2, p=0,008). According to ROC analysis, the threshold value of EM β-adrenergic reactivity corresponding to rfHTN was ≥44,8 conventional units (sensitivity — 69,2%, specificity — 64,5%, area under the ROC curve — 0,687). The mean EM β-adrenergic reactivity in the rfHTN group did not have a direct relationship with the LV mass index, but correlated with increased pulse pressure.Conclusion. RfHTN is associated with higher EM β-adrenergic reactivity values than in patients with rHTN, which may indirectly confirm more pronounced sympathetic activity and explain the higher prevalence of LVH, realized through an increase in vascular stiffness and load on the LV.